1970
DOI: 10.1111/j.1432-1033.1970.tb01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Über den Einfluß von Insulin auf die Alaningluconeogenese in der isoliert perfundierten Leber von New Zealand Obese Mice

Abstract: The influence of insulin and fat-rich diet on the alanine gluconeogenesis was investigated on isolated perfused livers of 3l/,-4 month-old male New Zealand obese mice (NZO-mice). White mice were taken as controls for an insulin effect. Glucose tolerances of NZO-mice were distinctly changed compared with those of white mice. Insulin inhibited gluconeogenesis in the livers of white mice in the same way as in the livers of rats. No insulin effect could be demonstrated out in livers of NZO-mice, however. This resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…During the clamp, the NZC mice suppressed completely, whereas the NZO mice continued to produce glucose, consistent with hepatic insulin resistance. This confirms the previous finding of Rudorff et al (25), who showed that, when livers from adult mice were perfused in situ, hepatic glucose release could be modestly reduced by insulin in the control mice, but there was no decrease in NZO mice. They concluded that adult NZO mice have hepatic insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…During the clamp, the NZC mice suppressed completely, whereas the NZO mice continued to produce glucose, consistent with hepatic insulin resistance. This confirms the previous finding of Rudorff et al (25), who showed that, when livers from adult mice were perfused in situ, hepatic glucose release could be modestly reduced by insulin in the control mice, but there was no decrease in NZO mice. They concluded that adult NZO mice have hepatic insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Most importantly, the data reveal that marked changes in the hepatic gene expression take place in insulin-resistant mice, in particular an induction of genes involved in lipid synthesis in the insulin-resistant population. This profound dysregulation appears to reflect the biochemical basis of the previously described (Subrahmanyam 1960, Rudorff et al 1970, Veroni et al 1991 severe hepatic insulin resistance of the NZO mouse.…”
Section: Discussionmentioning
confidence: 70%
“…NZO mice exhibit a markedly increased gluconeogenesis which is resistant to insulin (Rudorff et al 1970). Accordingly, transcript levels of PEPCK and G6 Pase were found upregulated in the diabetic and, to a lesser extent, also in the insulin-resistant cluster of backcross mice (Fig.…”
Section: Expression Of Gluconeogenic Enzymes In Hyperinsulinemic Micementioning
confidence: 84%
See 2 more Smart Citations